Financial Remittance and Growth in Nigeria: Does Financial Development Matter? - Okunade, Solomon O.; Afolabi, Adegboyega R.; Adeyemi, Oluwole J.; Olawumi, Adekunle T. (NIU Journal of Humanities; Vol 8 No 3 (2023): NIU Journal of Humanities, Vol. 8 No. 3, September 2023, 2023)
This study explores the complex relationship between financial remittances, financial development, and economic growth in Nigeria by investigating whether financial development serves as a mediator in the effect of remittances on Nigeria's economic performance. Thus, this present study focuses on the interactive effect of financial remittances and financial development on economic growth in Nigeria using secondary data for the periods of 1984 to 2022. The results of the Dynamic Ordinary Least Squares (DOLS) and Fully Modified Ordinary Least Squares (FMOLS) showed that, individually, remittances do not significantly increase economic growth in Nigeria, but when we considered the moderated effect of financial development, remittances become growth-enhancing in Nigeria. The findings reveal a positive and statistically significant interactive effect of remittances and financial development on economic growth, confirming the role of remittances as a source of external finance that stimulates domestic investment and consumption. Furthermore, the study provides compelling evidence supporting the mediating role of financial development in this relationship. A well-developed financial sector, characterized by depth, efficiency, and access, enhances the positive impact of remittances on economic growth. In light of these findings, the study underscores the importance of policies aimed at fostering financial inclusion, promoting financial literacy, and expanding access to formal financial services. These measures empower remittance recipients to make informed and productive financial decisions, thereby maximizing the developmental benefits of remittances. Keywords: Remittances; Growth; Financial Development; Nigeria; DOLS.